SEMUA ILMU ADA DALAM AL-QUR’AN: TELAAH PEMIKIRAN AL-SUYUTHIY DALAM AL-ITQAN FI ULUM AL-QUR’AN - Hibbi Farihin (IAIN Tulungagung, 2016)
One of the chapters (naw’u’) which was discussed interestingly in al-Itqan fi ‘Ulumal-Qur’an by Jalal al-Din al-Suyuthiy (d. 911 H) was the 65th chapter, namely fi al-‘Ulum al-Mustanbathah min al-Qur’an (the sciences that was based on the al-Qur'an). Among those who agree, they will show some evidence for the al-Suyuthiy thesis. While that does not agree, confirming the position of the al-Qur'an that is limited by time and space. This paper describes a number of data of al-Suyuthiy writting about his views on this matter. Hopefully, after understanding the arguments of al-Suyuthiy, every readers can determine their positions on that view. Keywords: Sciences resting on al-Qur’an, al-Suyuthiy, the position of the readers